2013
DOI: 10.1002/cctc.201200687
|View full text |Cite
|
Sign up to set email alerts
|

Unusually High Activity of Pt Islands on Rh(1 1 1) Electrodes for Ethanol Oxidation

Abstract: The electrooxidation of ethanol has been widely studied since its possible application in PEM cells. Many efforts have been devoted to disentangle its oxidation mechanism and how this mechanism depends on the ethanol concentration and the surface structure and composition of the electrode. [1][2][3][4] The goal is to obtain CO2 as final product at the lowest potential and the highest current. In the oxidation mechanism, three different products can be obtained: acetaldehyde, acetic acid and CO2, exchanging 2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
4
1
Order By: Relevance
“…The EOR activity of the structurally ordered HEIs is superior to that of most current electrocatalysts under the same test conditions 10,35,36 . Meanwhile, the electrocatalytic activity of Rh/C was also tested under the same conditions, and we found Rh had much less capacity for dehydrogenation than Pt (Figure ), which was consistent with the results reported in the literature 37,38 . In the process of electrochemical testing, we clearly observed that there were two peaks during the forward scanning.…”
Section: Electrochemical Propertiessupporting
confidence: 87%
“…The EOR activity of the structurally ordered HEIs is superior to that of most current electrocatalysts under the same test conditions 10,35,36 . Meanwhile, the electrocatalytic activity of Rh/C was also tested under the same conditions, and we found Rh had much less capacity for dehydrogenation than Pt (Figure ), which was consistent with the results reported in the literature 37,38 . In the process of electrochemical testing, we clearly observed that there were two peaks during the forward scanning.…”
Section: Electrochemical Propertiessupporting
confidence: 87%
“…In all cases, the current diminishes significantly and no change in the onset potential can be detected. Although it has been reported that PtRh alloys increase the CO2/acetaldehyde ratio in ethanol oxidation [15,23], the net effect observed here is a diminution of the total current. At this respect, it is worth noting that Rh atoms are exclusively adsorbed at the surface of Pt nanoparticles, that is, Rh decorated Pt surface is formed, whose behavior can be different from that observed for a PtRh surface alloy.…”
contrasting
confidence: 56%
“…In previous studies, Sn and Ru deposition on stepped surfaces showed some enhancement for the oxidation to CO2 [21,22], whereas Pt deposited on Rh electrodes also shows increased activity for the C-C bond scission [23]. In addition, some works have demonstrated the improvement in the carbonate formation when Pb atoms are adsorbed on polycrystalline Pt surfaces in alkaline solutions [24,25].…”
mentioning
confidence: 98%
“…Figure a and Figure S11 (Supporting Information) show the ethanol electrooxidation curves of different electrocatalysts with the current density normalized to the Pt mass and the ECSA, respectively. The Rh wavy NWs are inactive for EOR (Figure S12, Supporting Information), because Rh has much less capacity for dehydrogenation than Pt . Therefore, the activities for ethanol electrooxidation on these Rh@Pt n L NW/C catalysts are completely stemmed from the outer Pt shells.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the onset potential for generating CO 2 was lower on the catalysts with less Pt atomic layer numbers. In Rh‐Pt bimetallic heterosystems, the strain and ligand effects from the Rh subsurface is a key factor for weakening Pt–intermediate binding strength (such as PtCO) to ease their oxidation . As the in situ FTIR spectra shown, no obvious CO L band can be observed on the Rh @ Pt 1L NW/C and Rh @ Pt 3.5L NW/C catalysts, while a tiny CO L signal and a larger one can be found on the Rh @ Pt 5.3L NW/C and the Pt/C, respectively.…”
Section: Resultsmentioning
confidence: 99%